PENGARUH TRANSPARANSI KEBIJAKAN PUBLIK TERHADAP PENGETAHUAN DEWAN TENTANG ANGGARAN DENGAN PARTISIPASI MASYARAKAT SEBAGAI VARIABEL MODERASI - Siswanto Siswanto; Yundy Hafizrianda; Alfiana Antoh (Universitas Cenderawasih, 2016)
The Influencing of Public Policy Transparency for Improving the Capability on Budget Public Participation for the Member of Parliaments by Using Moderation Variable. (Case study of Member of Parliament Keerom). The purpose of the study was to investigate the effect of public policy transparency on improving the understanding of Member of Parliament in relation to public budgeting. Survey was conducted to obtain data where the author distributed questionnaires to the respondents. By using regression equation, the study found that the influencing of transparency public policy on the capability of the Member of Parliaments was a significant where indicated the t value (1.350) higher than t table (0.188) with the significant level 0.05. In addition, the influencing of community participation as variables moderate and transparency in public policy showed that there was a positive relationship between transparency public policy and capability of the Member of Parliament on budget.